2021
DOI: 10.1038/s41598-020-80523-7
|View full text |Cite
|
Sign up to set email alerts
|

Long-term risk of primary liver cancers in entecavir versus tenofovir treatment for chronic hepatitis B

Abstract: It remains controversial whether entecavir (ETV) and tenofovir disoproxil fumarate (TDF) is associated with different clinical outcomes for chronic hepatitis B (CHB). This study aimed to compare the long-term risk of ETV versus TDF on hepatocellular carcinoma (HCC) and intrahepatic cholangiocarcinoma (ICC) in CHB patients from a large multi-institutional database in Taiwan. From 2011 to 2018, a total of 21,222 CHB patients receiving ETV or TDF were screened for eligibility. Patients with coinfection, preexisti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
43
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 13 publications
(44 citation statements)
references
References 39 publications
1
43
0
Order By: Relevance
“…A random effects model yielded an uHR of 0.83 (95% CI: 0.71-0.97; I 2 = 52%, P = 0.009; Fig. 3a) in 14 studies including PSM cohorts 9,10,12,[14][15][16][17][18]22,23,26,28,46,47 and aHR of 0.78 (95% CI: 0.58-1.04; I 2 = 48%, P = 0.06) in 8 such studies (Fig. 3B).…”
Section: Meta-analysismentioning
confidence: 98%
“…A random effects model yielded an uHR of 0.83 (95% CI: 0.71-0.97; I 2 = 52%, P = 0.009; Fig. 3a) in 14 studies including PSM cohorts 9,10,12,[14][15][16][17][18]22,23,26,28,46,47 and aHR of 0.78 (95% CI: 0.58-1.04; I 2 = 48%, P = 0.06) in 8 such studies (Fig. 3B).…”
Section: Meta-analysismentioning
confidence: 98%
“…A multicenter retrospective cohort study from Taiwan analyzed 7,248 patients. The HCC incidence rates of ETV and TDF groups were statistical similar in the whole cohort (aHR, 0.82; 95% CIs, 0.66–1.02; P =0.078) and in the PSM cohort (aHR, 0.83; 95% CIs, 0.65–1.06; P =0.129) [ 13 ].…”
Section: Entecavir and Tenofovir Equally Prevents Hccmentioning
confidence: 99%
“…Based on the above studies, the clinical data of patients with hepatitis B cirrhosis after TIPS treated with different antiviral drugs were retrospectively analyzed in this study. Before this study, many studies[ 23 - 27 ] in the past 2 years have explored the effects of different antiviral drugs on the long-term occurrence of HCC in patients with CHB, most of which are retrospective cohort studies, and some were systematic reviews and meta-analyses, with non-unified conclusions. However, it can be concluded that nucleotide drugs (represented by TFV) are equal or superior to nucleoside analogues (represented by ETV) in the long-term risk of HCC, especially in some patients with high-risk factors for HCC, such as compensated cirrhosis or decompensated cirrhosis.…”
Section: Discussionmentioning
confidence: 99%